Presentation of the Israeli date palm plantation - Bernstein Z. (Le palmier dattier dans l'agriculture d'oasis des pays méditerranéens, 1993)
The region of Israel was famous for its high quality date culture during the 1st century AD. Date culture was totally destroyed by the end of the 10th century. Date culture in this country was renewed by the introduction of the high quality cultivars of Iraq, Egypt and North Africa. The cultivated area stretches along the Syrian-African rift valley from the gulf of Aqaba to the Sea of Galilee. Today the plantations consist of about 200,000 date palms (female), about half of them young palms. Planting objectives have changed due to the market demands from the Iraqi cultivars through 'Deblet Noor' to 'Medjool'. The spacing between palms in the plantations is 9x9 m and crop is 80-120 kg per tree of the dry cultivars to 150-300 kg per tree of the fresh ones. All growers are members of the organization 'Hadiklaim' which buys their fruit and markets it. The marketing target is to export about half of the total crop. Research and guidance are focused on increasing the crop and the profit of growers.
Journées Internationales d'Elche sur le Palmier Dattier dans L'Agriculture d'Oasis des Pays Méditerranéens, 25-27 Apr 1995, Elche (Spain)